Maintenance of antibody response to diphtheria/tetanus vaccine in patients aged 2-5 years with polyarticular-course juvenile idiopathic arthritis receiving subcutaneous abatacept - Brunner, Hermine I.; Tzaribachev, Nikolay; Cornejo, Gabriel Vega; Joos, Rik; Gervais, Elisabeth; Cimaz, Rolando; Calvo Penadés, Inmaculada; Cuttica, Rubén; Lutz, Thomas; Quartier, Pierre; Gandhi, Yash; Nys, Marleen; et al. (Pediatric rheumatology, 2020)
Patients with polyarticular-course juvenile idiopathic arthritis (pJIA), receiving disease-modifying anti-rheumatic drugs with immunosuppressive effects, may be at increased risk of vaccine-preventable infections. This substudy assessed protective antibody responses to diphtheria and tetanus vaccination given prior to study enrolment in patients with pJIA.